Validitas dan Praktikalitas E-Modul Pelatihan Mikrotik Guru Teknik Komputer Jaringan - Khairul Anshari; Kasman Rukun; Asrul Huda (Ikatan Ahli Informatika Indonesia (IAII), 2019)
The achievement of the Teacher Competency Test (UKG) results has not yet reached the expected percentage target. Based on the analysis, teachers need to increase their knowledge and skills about microtics. The module that is commonly used is a pdf format module that contains power point slides, the module does not have a more detailed description of the proxy use steps. This study aims to develop microtic training modules and reveal their validity and practicality. This type of research is development research using plomp and nieveen models, namely preliminary research, prototyping stage, and assessment phase. The instrument used was a questionnaire of validity and practicality. The results of the module validity test research by three module experts obtained results in the valid category. The validation of the material by three experts, the material was obtained with a valid category. Based on practicality tests by network computer engineering teachers at SMKN 2, SMKN 3, SMKN 5, SMKN 6 and SMKN 8 Padang shows that the module has a very high practicality category. Based on the results of the study, it can be concluded that the microtic training e-module is considered valid by experts as well as practical by instructors and trainees